Policy responses to the COVID-19 pandemic in the Manitoba grocery sector: a qualitative analysis of media, organizational communications, and key informant interviews - Natalie D. Riediger; Joyce J. Slater; Kelsey Mann; Bhanu Pilli; Hannah Derksen; Chantal Perchotte; Avery L. Penner (BMC, 2022)
Abstract Objectives The COVID-19 pandemic has impacted all aspects of the food system, including the retail grocery sector. We sought to (objective 1) document and (objective 2) analyze the policies implemented in the grocery sector during the first wave of the pandemic in Manitoba, Canada. Methods Our qualitative policy analysis draws from organizational communications (websites and social media) (n = 79), news media articles (n = 95), and key informant interviews with individuals (n = 8) working within the grocery sector in urban and rural, Manitoba. Media and communications were extracted between March 9-May 8, 2020 and interviews were conducted in July-August, 2020. Results Newly implemented policies due to the pandemic fell under four inter-related themes: Employee health and wellbeing, Safety measures, Operational measures, and Community support. Employee health and wellbeing included sub-themes of financial and social support, health recommendations and protocols, and new employee guidelines. Safety measures encompassed numerous policies pertaining to sanitation, personal protection, transmission prevention, physical distancing, and limiting access. Overall, new policies were discussed as effective in making grocery shopping as safe as possible given the situation. Compliance and enforcement, employee teamwork, and support for employees were key themes related to perceptions of policy success in a challenging and inequitable context. Nevertheless, government support and communication was needed as well to ensure safety within the grocery sector. Conclusions The grocery sector reacted to the pandemic with the swift implementation of policies to address food supply issues, prevent transmission of the virus, support their employees as essential workers, and better serve high-risk populations.